2023
DOI: 10.3390/medicina59040683
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chinese Herbal Medicine Use and Risk of Sjögren’s Syndrome in Patients with Rheumatoid Arthritis: A Retrospective, Population-Based, Nested Case-Control Study

Abstract: Background and Objectives: Sjögren’s Syndrome (SS) is a common extra-articular feature among subjects with rheumatoid arthritis (RA). While Chinese herbal medicine (CHM) has been used to treat symptoms of RA for many years, few studies have examined its efficacy in guarding against the SS onset. This study aimed to compare risk of SS for RA patients with and without use of CHM. Materials and Methods: Data obtained for this nested case-control study were retrieved from Taiwanese nationwide insurance database fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Thus, dryness is both a pathologic factor and a pathologic result. It has been demonstrated that TCM has achieved notable clinical efficacy in the diagnosis and treatment of SS combined with RA, especially in controlling disease progression and recurrence [17] . However, since traditional observational research fails to exclude confounding factors, whether there is a causal relationship between SS and RA remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dryness is both a pathologic factor and a pathologic result. It has been demonstrated that TCM has achieved notable clinical efficacy in the diagnosis and treatment of SS combined with RA, especially in controlling disease progression and recurrence [17] . However, since traditional observational research fails to exclude confounding factors, whether there is a causal relationship between SS and RA remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Western medicine, Chinese medicine and complementary therapies have been extensively investigated for their potential use in treating rheumatic diseases [ 9 , 10 ]. Liao et al demonstrated that patients with RA using Chinese medicine could reduce the risk of developing Sjögren’s Syndrome, a common extra-articular manifestation of RA [ 11 ]. Regarding complementary therapy usage, our previous study found that more than 85% of Taiwanese patients with SLE used complementary therapies on a regular basis [ 12 ].…”
mentioning
confidence: 99%